Creación de la plataforma Cundi-Travel, enfocada a promover el turismo en Cundinamarca - Latorre Pelaez, David Guillermo; Torres Garzón, Daniel Felipe (Universidad Antonio Nariño, 2021)
This document presents the development of a project that provides tourist information about Cundinamarca, in order to publicize some little-visited destinations in the region. The idea The main thing is to be able to connect people who go out by car to visit places near Bogotá, with service providers that can benefit from it, such as hotels, parking lots, restaurants and people who subsist from sharing the cultural and historical content of the 116 municipalities that Cundinamarca currently has.